ANALYSIS OF ELEVENTH-GRADE VOCATIONAL HIGH SCHOOL STUDENTS PROBLEM-SOLVING ABILITY IN LINEAR PROGRAMMING - Sari, Nurfatma; Roza, Yenita; Yuanita, Putri (Universitas Tanjungpura, 2025)
This research is motivated by the fact that problem-solving ability is a fundamental skill that students must possess. However, field observations indicate that students